2017
DOI: 10.1021/acs.analchem.7b01221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Antihapten VHH Selection Strategies for the Development of Highly Sensitive Immunoassays for Microcystins

Abstract: Owing to their reproducibility, stability, and cost-effective production, the recombinant variable domains of heavy-chain-only antibodies (VHHs) are becoming a salient option as immunoassay reagents. Recently, there have been several reports describing their application to the detection of small molecules (haptens). However, lacking the heavy-light chain interface of conventional antibodies, VHHs are not particularly apt to bind small analytes and failures are not uncommon. Here we describe the construction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 23 publications
(35 reference statements)
0
38
1
Order By: Relevance
“…This flexible nature of the M2e peptide could explain why it appears to be difficult to isolate a VHH that recognizes the N-terminal part of M2e. Moreover, due to the absence of the light chain, VHHs typically bind to concave epitopes rather than to convex or protruding peptide termini (59,60). Nevertheless a few VHHs directed against linear peptides have been described (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…This flexible nature of the M2e peptide could explain why it appears to be difficult to isolate a VHH that recognizes the N-terminal part of M2e. Moreover, due to the absence of the light chain, VHHs typically bind to concave epitopes rather than to convex or protruding peptide termini (59,60). Nevertheless a few VHHs directed against linear peptides have been described (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using the cyanotoxin microcystin-LR (995 Da) as a model hapten and a high-throughput screening, we compared this way of selection with two additional strategies. We found that selecting for Nbs with the slowest k off for the immobilized hapten allowed us to attain a detection limit of 50 pg/mL, which was 10-fold better that the one obtained using the Nbs isolated by competitive selection ( 90 ). While the usefulness of this approach still needs to be demonstrated for other haptens, alternative methods for the selection of anti-hapten Nbs are needed, because, conversely to what happens with other antigens, failures in the generation of Nbs that recognize small molecules in solution are common ( 89 ).…”
Section: When Being Small Mattersmentioning
confidence: 83%
“…Nbs consists of four conserved framework regions and three antigen-binding loops, known as the complementarity determining regions (CDRs). The particularly long CDR3 rends the paratope its convex shape, building protrusions that can reach cryptic epitopes often not accessible to cAbs [27,28,31,32].…”
Section: Nanobodies—single Domain Antibodiesmentioning
confidence: 99%